Особенности подхода к вопросу собственности в Приднестровской Молдавской Республике - Furmaniak, Piotr (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the peculiarities of the right to property in the Republic of Moldova. The author focus on the property rights law system of the Republic of Moldova with a special emphasis on the fragility of state institutions and the significant role of businesses environment.